Prioritizing Investments in Climate-Smart Agriculture in Guatemala - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
A workshop held in Guatemala City brought together a broad group of stakeholders to refine the initial list of practices, validate the overall objectives and then evaluating the criteria of the three pillars of climate-smart agriculture (adaptation, mitigation and productivity). Photos: J.L.Urrea (CCAFS)